Comunicación corporativa del club deportivo universidad técnica de Cotopaxi para mejorar la relación y vínculos con sus públicos de interés - Naranjo Huera, Vilma Lucia (2014)
Among the main characteristic of the strategic communication stand out to admit to the planned actions as an appropriate way of management of perceptions for, in a conscious way, to interact with its public of interest and sectors of influence, therefore that all communication efforts are integrated to achieve the proposed objectives, these can be business institutional. The sports club UTC has had an important participation in the national football championship which has allowed that it to go up to rise inside the categories of professional football in the last 6 years from its foundation in 2007, has left relegated the communication no by lack of interest, it is rather because of a lack of resources. The corporate communication is a strategy that allows to improve the relations and links with public, in this case of study with the citizenship of Cotopaxi province, for this reason capture the fans and public relations necessary to its continued growth inside the Ecuadorian football and can get a place yearn in the series A. To deal the theme will arises of initial way to realize an approach to the case study "Sporting Club Cotopaxi Technical University" to analyze corporate communication as an element to improve the relationship and links with public interest. With a quali-qualitative methodology analyzes the context of professional football and perception of its public. The analysis of the present situation of the club with based in the FODA this analysis allowed to develop a communication plan that design a route to manage the communication address of the club. In the present work achievement to identify the variables and reaction that perceived public to be cared for in their informational needs and demands.